HOAX SERBUAN TKA DARI CHINA: KEPANIKAN MORAL DAN BUDAYA KETAKUTAN - Triyono Lukmantoro (Masyarakat Indonesia, 2018)
At the end of December 2016, the hoaxes emerged stating that there were about ten million, even twenty million, illegal foreign workers from China who were invading Indonesia. Although the hoaxes have been strongly denied and regarded as slander by the government, in fact, the hoaxes were already spreading. One of the sites that produce these hoaxes is Postmetro. This article is a textual review of various hoax titles displayed by Postmetro. The results of this study show that the various hoaxes are no more the practices of "Frankenstein journalism", that is simply taking news and polishing the title to be so provocative from other media sources. The illegal foreign workers from China are described as the foreigner who exacerbates the life of national laborers. This shows that illegal foreign workers from China were positioned as a figure that caused the moral panics. In addition, they are also described as demons of the people (folk devils) who deserve to be cursed and expelled from Indonesia for creating fear and pathological character.